Autoimmune complexity: A case report of immune thrombocytopenia (ITP) with coexistent positive autoimmune markers and multidisciplinary challenges - Ali, Tariq; Rattani, Salma; Shaikh, Faheem (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
This case study explores a complex clinical presentation of an 85-year-old male diagnosed with immune-mediated thrombocytopenia (ITP) with coexistent positive autoimmune markers. A multidisciplinary approach was crucial in managing the patient, involving hematology, rheumatology, urology, and respiratory specialists. Despite tailored treatments, including platelet transfusions, immunosuppressive therapies, and antibiotics, the patient developed complications including hospital-acquired pneumonia, pulmonary infection, and acute kidney injury. Extensive discussions with the family led to the decision to transition the patient to comfort care, emphasizing the challenges in managing complex cases and the importance of a comprehensive care plan.